Factors Associated with Fire Preparedness of UPTD Employees at the Kenali Besar Community Health Center - Mutiara Asrie Dravika; Marta Butar Butar; David Kusmawan; Budi Aswin; Ashar Nuzulul (Formosa Journal of Multidisciplinary Research, 2024)
Fire preparedness is an emergency response effort to the danger of fire. Low fire preparedness can result in large losses from fire incidents. This research aims to determine the factors related to fire preparedness among employees at the Kenali Besar Community Health Center. This research is a quantitative study with a cross-sectional design. Carried out in February 2024 with a population of 63 employees. Samples were taken using the total sampling technique. Research analysis uses the chi-square test. The results of statistical tests show that there is a relationship between knowledge and fire preparedness (p= 0.007) and infrastructure and fire preparedness (p= 0.009). It was concluded that the factors related to preparedness among Kenali Besar Community Health Center employees were knowledge and infrastructure. There is a need to increase knowledge and infrastructure as well as carry out regular training and supervision for community health centers.